PENGEMBANGAN MEDIA PEMBELAJARAN WORABUD (WORDWALL KERAGAMAN BUDAYA) PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SD - Lintang Kusumawardani; Wawan Shokib Rondli; Denni Agung Santoso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the limited use of learning media at SDN Mlatiharjo 2, which still relies on worksheets, whiteboards, and simple slides, resulting in low student engagement. The study aims to develop Wordwall-based learning media (WORABUD) for Pancasila Education subject on Cultural Diversity material for Grade V and to test its feasibility. The method used is Research and Development (R&D) with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The research subjects were 22 Grade V students. Validation was carried out by media experts, material experts, teachers, and students. The results showed that WORABUD was rated 'very feasible' by all validators. The media effectively increased student engagement through interactive game-based activities relevant to cultural diversity content. WORABUD is accessible, visually attractive, and provides an enjoyable and effective learning experience.